Husband responses towards birth preparedness, complications readiness, and associated factors in southern Ethiopia: the case of Kena District - Belda Negesa Beyene; Korra Gochano Hirra; Negeso Gebeyehu Gejo; Derese Eshetu Debela (BMC, 2024)
Abstract Background Birth preparedness and complication readiness is a holistic approach that empowers mothers and families with the knowledge, attitude, and resources to alleviate potential challenges during childbirth. Despite its benefits, husbands' participation in maternal care differs significantly between countries and regions. There is a lack of previous studies that look at husbands' responses to birth preparedness and complication readiness in the research area. Thus, the primary goal of this study is to find out how husbands who have wives with infants under 12 months old feel about birth preparation, readiness for problems, and its associated factors. Methods A community-based cross-sectional study design was conducted from May 30 to July 29, 2022. Simple random sampling was employed to select 499 husbands. An interviewer-administered, structured, and pretested questionnaire was used to collect the data. Data entry and analysis were performed using Epi Data version 4.6 and SPSS version 25, respectively. We used multivariable logistic regression to find statistically significant factors. P-values less than 0.05, 95% confidence intervals, and adjusted odds ratios are used to declare statistical significance. The findings were shown in figures, tables, and text. Results The study found that 55.9% (95% CI: 51.4 to 61.4%) of husbands responded to birth preparedness and complication readiness. This response was significantly associated with being employed (AOR = 3.7, 95% CI: 2.27-5.95), engaging in self-business (AOR = 5.3, 95% CI: 2.34-12.01), having wives who delivered in health facilities (AOR = 7.1, 95% CI: 3.92-12.86), accompanying wives for antenatal care (AOR = 2.2, 95% CI: 1.39-3.56), possessing good knowledge of danger signs during labor (AOR = 2.0, 95% CI: 1.08-3.74) and the postnatal period (AOR = 7.1, 95% CI: 3.14-16.01). Interestingly, residents living near a health facility (AOR = 0.6, 95% CI: 0.39-0.97) were less likely to respond. Conclusion The present study found that nearly 6 out of 10 husbands actively responded in terms of birth preparedness and complication readiness. While husbands in this study showed some involvement in birth preparedness and complications, it is good when compared to studies carried out nationally. To improve this, educating husbands by focusing on the danger signs and their role in childbirth is recommended.